El tangram para desarrollar el ámbito lógico-matemáticas, en los niños de inicial II de la escuela de educación general básica Julio María Matovelle de la ciudad de Loja, período académico 2018-2019 - Granda Alulima, Tatiana Fabiola (2020)
The research work entitled THE TANGRAM TO DEVELOP THE LOGICAL-MATHEMATICAL FIELD AMONG CHILDREN OF INITIAL II OF BASIC GENERAL EDUCATION AT JULIO MARÍA MATOVELLE SCHOOL IN THE CITY OF LOJA, DURING THE 2019-2020 SCHOOL YEAR, has as general objective: To base the importance of the Tangram to develop the logical-mathematical field among children of initial II, the literature review addressed the Tangram as the first variable and the mathematical logical field as the second one; the methods considered in this research work are the scientific, the descriptive, the statiscal, the inductive- deductive and the experimental method; The techniques and instruments used were the survey applied to teachers of the initial level and the rating scale based on the mathematical logic skills of the initial education curriculum 2014, sub-level II of 4-5 years. The target population consisted of 21 people, two teachers and 19 children of the initial level II, the results obtained in the diagnosis showed that 49% of children are in the development process; with the intention of supporting the progress of the mathematical logic field an alternative proposal was designed and executed, which was entitled "If you want to create, start by playing"; Once the execution was completed, the post-test was applied, the results increased by 39,1%, which mean the children mastery of the skills. The recreational activities carried out with Tangram contributed significantly to develop the children’s mathetical field. At the same time, these results ratify the proposal. It is recommended to use new teaching resources that require the development of children’s notions, skills, and abilities.